Utilizing machine learning to project the nancial outcomes of reconnecting with potential customers of the same industry - Hossain, Shoumik; Fahmiduzzaman, Quazi; Payel, Nehrin Siddique; Hossain, Mohammad Shahriar; Hossain, Nabil (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.